Consumer behaviour and material culture in Britain, 1660-1760 - Weatherill, Lorna (Routledge, 1996)
This is a detailed study of the material lives of the middle-classes in the pre-industrial era, a period which saw considerable growth in consumption. Weatherill has brought her research in her very important study completely up-to-date.